The Effect of Job Stress and Work Environment on Employee Performance Through Job Satisfaction at Airports in the Manokwari Region - Kumendongl, Frengki; Christian, Ferdinandus; Astini, Rina (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the effect of work stress and work environment on employee performance through job satisfaction at Banadara in the Manokwari Region. This research was conducted using a quantitative approach with an explanatory research design to determine the direct effect of work stress variables, work environment and job satisfaction on employee performance and the indirect effect of work stress and work environment on employee performance through job satisfaction at the Airport in the Manokwari Region. The population in this study were 138 people and a sample of 102 using the Slovin formula. Data collection techniques using questionnaires and to test the hypothesis using Partial Least Square (Smart PLS). The results showed that work stress has a significant effect on employee performance; Work environment has a significant effect on employee performance; Job satisfaction has a significant effect on employee performance; Work stress has a significant effect on job satisfaction; Work environment has a significant effect on job satisfaction; Job satisfaction mediates the effect of work stress on employee performance; Job satisfaction mediates the effect of work environment on employee performance.